DAYASAING KOMODITAS HORTIKULTURA NEGARA BERKEMBANG DAN NEGARA MAJU DI PASAR INTERNASIONAL - Eko Purwo Santosa; Muhammad Firdaus; Tanti Novianti (IPB University, 2016)
Horticulture is one of the agricultural sub-sector consisting of vegetables, fruits, biofarmaka mplants (medicinal plants) and floriculture (ornamentals) became one of the commodities subject of international trade, which the demand is increasing in line with increasing household income and growth population. During the period 2005-2014, the average growth value of horticultural exports of developing countries amounted to 69,81 percent higher than the average growth of exports in developed countries as big as 40,78 percent. The global trading of horticulture is faced with price volatility and trade barriers problems. In addition, the increasing demand of these commodities also in line with the increase in household incomes and population growth. Therefore, this study aimed to analyze the competitiveness of horticulture commodities in the international market and the factors that influence trade flow. The results of Export Product Dynamic (EPD) show that there are two horticultural export commodity that has dynamic market position in world market, there are bananas (HS.080300) and pineapples (HS.080430). Generally, the panel data analysis results show that prices, trade barriers, population, real GDP per capita, economic distances, and real exchange rates significantly affect export volumes. Keywords: Competitiveness, Exports, Horticulture, Gravity model